54‐4: Distinguished Student Paper: Low‐Diffraction Transparent μLED Displays with Optimized Pixel Structure. Issue 1 (28th June 2022) - Yang, Qian; Yang, Zhiyong; Lan, Yi-Fen; Wu, Shin-Tson
Abstract : A semi‐analytical model is built based on diffraction theory and human angular resolution to quantitatively evaluate the diffraction effect of transparent displays, including micro‐LED and OLED. By optimizing the pixel structures within a 2×2‐pixel size region, the relative diffraction intensity is reduced by 42% at the 50% aperture ratio regardless ofpixel density.